A documentation study of the restoration process of Al-Haddam heirs’ house in Bab Zir – Tlemcen city in western Algeria - Othman Yebdri; Labtar Qadda (Revista de Expresión Gráfica en la Edificación)
The old city of Tlemcen, west of Algeria, has received many restoration projects, including various architectural monuments and archaeological sites dating back to different periods of time, especially those that the city witnessed on its selection as the capital of Islamic culture in 2011. However, due to the large number of simultaneous restoration projects, the limited period for their implementation and the lack of actors with expertise in this field, many of them has been postponed to a later date. Among the most important of these postponed projects is Bab Zir Square, one of the most important residential neighborhoods in the old city and its historic buildings. In 2023, it received its share of restoration operations, and the house of the heirs of Al-Haddam is one of the most prominent of these buildings. Through this study, we will document the process of restoring this building by tracing the stages involved; We start with an accurate diagnosis of the condition of the building before restoration, then the restoration phase, by tracing the work that affected the various architectural and structural sections, and finally the post-restoration phase to determine the status and condition of the building after the completion of the work, with the aim of making this study a reference for future research and studies.